(untitled) (Educational Dimension, 2019)
The study is aimed at theoretical substantiation, development and experimental testing of methods of applying mobile technologies by university students. The objectives of the study imply adapting mobile testing systems and mobile means of multimedia development for using in the classroom environment at universities. The research object is application of mobile ICT to the educational process. The research subject is methods of applying mobile testing systems and mobile means to conduct practical classes at the University. The studies of Ukrainian and foreign researchers dedicated to the question of using mobile ICT for the university educational process were analyzed. Mobile testing systems are defined as a variety of mobile software support aimed firstly to measure students’ academic results, which enables to automatize the process of both current and final control through applying modern testing means, and secondly to intensify the educational process comprehensively. It is found that mobile means of multimedia development are to fulfill the principles of multimedia, space vicinity, time contiguity, coherence, modality, excessiveness, personalization, interactivity signalization and individual distinctions. The authors have developed the methods of applying mobile testing systems by taking Plickers system, as the one providing the opportunity to arrange a rapid feedback between a lecturer and both an academic group and an individual student. The system also allows conducting mobile surveys, in-class general questioning and instant control of students’ attendance. The authors have developed methods of applying mobile tools of multimedia development through using augmented reality. The comparative assessment of functionality of mobile testing systems and mobile means of developing augmented reality multimedia was held. Efficiency of the developed technology was experimentally tested and confirmed.